2003
DOI: 10.1086/374880
|View full text |Cite
|
Sign up to set email alerts
|

Subaru Deep Survey. IV. Discovery of a Large-Scale Structure at Redshift ≃5

Abstract: We report the discovery of a large-scale structure of Lya emitters (LAEs) at based on wide-field z p 4.86 imaging with the prime-focus camera (Suprime-Cam) overdensity ( ), which may be the progenitor of a cluster of galaxies. Assuming this circular region to be d p 2 S a sphere with a spatial overdensity of 2, we compare our observation with predictions by cold dark matter models. We find that an flat model with predicts the number of such spheres consistent with the Q p 0.3 j p 0. 9 0 8 observed number … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
122
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 31 publications
15
122
0
Order By: Relevance
“…Adopting the normalization of the power spectrum σ 8 = 0.81 (Komatsu et al 2011) and the approximation for the mass variance with the top-hat window, σ (R) = σ 8 (R/r 8 ) −β (Mo et al 2010) with β ≈ 0.7 (CDM shape parameter Γ = 0.2), and the linear growth rate in the non-zero cosmological constant (Carroll et al 1992), ≈3.3 at z = 3.1, we obtain the σ (R) = (δρ/ρ 0 ) 2 1/2 at the corresponding comoving scale (R ≈ 32 Mpc) at z = 3.1 is ≈ 0.11. The observed density variation among the five general fields, (δN/N 0 ) LAE = −0.38 (SXDS-N) to + 0.21 (SDF), is comparable with the value, if we consider that the Lyα emitters trace mass distribution with the linear biasing factor b ∼ 2-6, as obtained in the previous study of Lyα emitters at z = 2-5 from the analysis of the twopoint correlation functions (Shimasaku et al 2003;Gawiser et al 2007;Guaita et al 2010). On the other hand, the density excess of the SSA22-Sb1 with (δN/N 0 ) LAE = 1.13 ± 0.01 even at this scale is unexpectedly large, more than ≈10× the mass fluctuation, which implies that the field is the very rare, >5σ LAE peak with b = 2 (Gawiser et al 2007).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Adopting the normalization of the power spectrum σ 8 = 0.81 (Komatsu et al 2011) and the approximation for the mass variance with the top-hat window, σ (R) = σ 8 (R/r 8 ) −β (Mo et al 2010) with β ≈ 0.7 (CDM shape parameter Γ = 0.2), and the linear growth rate in the non-zero cosmological constant (Carroll et al 1992), ≈3.3 at z = 3.1, we obtain the σ (R) = (δρ/ρ 0 ) 2 1/2 at the corresponding comoving scale (R ≈ 32 Mpc) at z = 3.1 is ≈ 0.11. The observed density variation among the five general fields, (δN/N 0 ) LAE = −0.38 (SXDS-N) to + 0.21 (SDF), is comparable with the value, if we consider that the Lyα emitters trace mass distribution with the linear biasing factor b ∼ 2-6, as obtained in the previous study of Lyα emitters at z = 2-5 from the analysis of the twopoint correlation functions (Shimasaku et al 2003;Gawiser et al 2007;Guaita et al 2010). On the other hand, the density excess of the SSA22-Sb1 with (δN/N 0 ) LAE = 1.13 ± 0.01 even at this scale is unexpectedly large, more than ≈10× the mass fluctuation, which implies that the field is the very rare, >5σ LAE peak with b = 2 (Gawiser et al 2007).…”
Section: Discussionsupporting
confidence: 85%
“…More than a few high-density regions of the Lyα emitters and star-forming galaxies at high redshift have been studied (Keel et al 1999;Steidel et al 2000Steidel et al , 2005Shimasaku et al 2003;Palunas et al 2004;Hayashino et al 2004;Matsuda et al 2004Matsuda et al , 2009Matsuda et al , 2010 Kuiper et al 2010;Yang et al 2010). Among them, the structure at z = 3.09 in the SSA22 region, specifically the area around the original selected survey area at 22 h (Cowie et al 1990), is one of the most prominent and interesting ones.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Steidel et al (2000) used narrow-band imaging to map the extent of a large-scale structure at z ∼ 3.09, discovered in a survey for continuum-selected Lyman-break galaxies. Shimasaku et al (2003) serendipitously found a large-scale structure at z ∼ 4.9 while searching for Lyα emitters in the Subaru Deep Field. Their results demonstrate that Mpc-scaled structures have already formed by z ∼ 4.9 and that Lyα emitters must be very biased tracers of mass in the early Universe.…”
Section: Introductionmentioning
confidence: 98%
“…Bahcall et al 1997). The narrow-band imaging technique can efficiently select objects with a strong Lyα line in a narrow redshift range, and is therefore ideal for finding and investigating overdense regions at high redshift (Steidel et al 2000;Shimasaku et al 2003;Palunas et al 2004). For example, Steidel et al (2000) used narrow-band imaging to map the extent of a large-scale structure at z ∼ 3.09, discovered in a survey for continuum-selected Lyman-break galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…While this technique has been successful in observing large numbers of structures or protostructures in the high-redshift universe, it is not at all clear whether such environments are typical progenitors of lower redshift clusters or are exceptional in some way, which limits their usefulness in contextualizing results at lower redshifts. Additionally, narrow-band and spectroscopic searches of Lyman α emitter (LAEs) populations in (somewhat) random regions of the sky have revealed protostructures in the very high-redshift universe (e.g., Shimasaku et al 2003;Ouchi et al 2005;Lemaux et al 2009;Toshikawa et al 2012). However, such surveys cover rather limited portions of the sky and are only effective at observing overdensities of emission line objects, a population that, while being readily observed at high redshift because of the relative ease of obtaining redshifts of emission line objects, is the subdominant population in the early universe (see, e.g., Shapley et al 2003).…”
mentioning
confidence: 99%